Nursing Students’ Knowledge and Attitude on Consumption of Iron Supplement to Prevent Iron Deficiency Anaemia - Mira Trisyani; Ermiati E; Yanti Hermayanti; Restuning Widiasih; Tetti Solehati; Anita Setyawati (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
The World Health Organization (WHO) reported that the incidence of anemia in adolescent, especially in developing countries, remained high, including in young women in the West Java provinces. An alternative way to deal with anemia in adolescents is by fulfilling their daily nutrition, especially during menstruation. This study aimed to determine the knowledge and attitudes of nursing students related to the sources of iron supplement in Faculty of Nursing Universitas Padjdjaran. This study applied the descriptive quantitative approach. Samples were chosen using the purposive sampling method, and 197 students from three different years involved in this study. The respondents filled in the Gutman instrument to assess their knowledge and attitude. Results showed that 23.85% of respondent had a low understanding of iron supplement sources, 41,62% in the moderate level of understanding, and 34.51% of respondents had a high level of knowledge. In regard to respondents’ attitude, the majority of respondent had a good attitude (52,79%) and (47,20%) of them had the low attitude. This study informed that there was a group of student who risks of Iron deficiency anemia. It was because of unregular consumption of Iron tablet and their habit related to caffeine consumption that may be affected by iron’s absorption in their body. There is a need for a monitoring and implementation program to evaluate adolescents' intake including folic acid, iron supplement, and vitamin to improve hemoglobin levels.Keywords: Anemia, Attitude, Iron Deficiency, Knowledge